The role of self-regulatory skills in young talented athletes playing team sports - Jonker, L.; Elferink-Gemser, M. T.; Visscher, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Both in sports and academics it has been found that at the higher levels one typically finds more athletes or students with superior selfregulatory skills (Cleary & Zimmerman, 2001; Zimmerman, 1986). Self-regulation reflects a combination of metacognitive attributes, i.e., planning, self-monitoring, evaluation, and self-reflection, and motivational attributes, i.e., effort and self-efficacy (Ertmer & Newby, 1996; Hong & O`Neill Jr., 2001). Unknown, however, is whether there is an association between these skills and: 1 sport competitive level and 2. level of education in highly talented athletes playing team sports. In total 120 talented athletes playing baseball, basketball, handball, field hockey or volleyball filled in a questionnaire for self-regulatory skills (Herl et al., 1999; Hong & O`Neill Jr., 2001; Howard et al., 2000; Peltier et al., 2006). Of them, 33 competed at international sport competitive level (mean age: 14.9 years ± 1.09 years) and 87 competed at national level (mean age: 13.9 yrs ± 1.01). Data were analysed using MANCOVA with the self-regulatory skills as dependent variables, sport competitive level and level of education as factors, and age as covariate. The results of the MANCOVA showed no significant differences (p>.05) on the six self-regulatory aspects for sport competitive level or level of education which may mean that at the `highest` sport performance levels a general feature as self-regulation is not discriminative. Yet, the possession of above average levels of self-regulation is a necessity for talented athletes in order to juggle the demands of their academic career with their extensive investments in sports (Moon, 2003). Although not statistically different, the results showed that the athletes competing at international level had higher scores on evaluation and self-reflection with moderate effect sizes: d=0.50 on both attributes. With regard to our findings, it appears prominent that sport specific characteristics make the difference between the international elites and those performing at national level within team sports. Further investigation is warranted with respect to individual sports in which self-regulation is closely related to sport specific psychological skills (Anshel, 1995). Nonetheless, our findings have important implications for people involved with talented athletes playing team sports. It would, for instance, be interesting to investigate in a longitudinal design whether self-regulation will enable promising athletes to optimally profit from their self-regulatory skills in their sports and academics.